Fabrication and characterization of polyethylene terephatate optical waveguides - SINGH, G; LOW, A; YONG, Y (2004)
In this paper, the fabrication and characterization of polyethylene terephatate (PET) thin film integrated optical waveguide is presented. Dip-coating technique has been used to fabricate the optical waveguide using PET. Various waveguide properties, such as mode effective refractive index, optical loss, dispersion and waveguide thickness as a function of temperature of waveguides have been reported. The optical loss are found to be <1 dB cm(-1).